Dynamic talker activity analysis - Shah, Asadullah; Abdullah Zammarh, Nuha (IIUM Press, 2011)
Speech activity and non-activity is a scenario in which each activity (talkspurt) and non-activity (silence) may vary in size. Some talkspurts may be many frames and others may be only a few frames long, considering each frame of speech of 20-30ms. In this chapter a dynamic talker activity analysis is provided through statistical measures to describe the dynamics of the speech sources